Integrating Green Human Resource Management and Green Supply Chain: A Systematic Literature Review in The Context of The Manufacturing Industry in Indonesia - Muh Idil; Istimaroh Istimaroh; Fenty Fauziah (CV. RADJA PUBLIKA, 2026)
The manufacturing sector in Indonesia plays a critical role in national economic growth, contributing significantly to GDP. However, it is also a major contributor to environmental degradation through greenhouse gas emissions and industrial waste. Faced with this paradox, companies are required to undergo a sustainability transformation that is both technical and cultural. This research aims to map and synthesize existing literature on the integration of Green Human Resource Management (GHRM) and Green Supply Chain Management (GSCM) as key determinants of sustainable performance. Using the Systematic Literature Review (SLR) method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, this study examines relevant empirical articles to identify relationship mechanisms, methodological trends, and research gaps. The results of the review indicate that GHRM serves as the foundation for building employees’ green capabilities and culture, which are then operationalized through GSCM practices to achieve holistic sustainability performance. This article makes a theoretical contribution by clarifying the role of GSCM as a mediator within the Ability-Motivation-Opportunity (AMO) framework and offers a framework for industry managers to align human resource policies with operational strategies. By integrating GHRM and GSCM, companies can achieve better environmental, economic, and social performance, ultimately fostering long-term sustainability. This study also highlights the challenges faced by the Indonesian manufacturing industry in implementing these practices and provides recommendations for overcoming these barriers through employee-driven innovation and strategic alignment.